Comparative analysis of psycho-physiological parameters of the deaflympic karate champion and healthy karate women - Ianchuk, K.; Tykhorskyi, O. (Path of Science, 2021)
The article compares psycho-physiological indicators of an elite athlete in karate - the champion of the Deaflympics and healthy, highly qualified athletes. The researched indicators were: work efficiency, degree of employment, mental stability, time of simple reaction to a moving object, reaction to a moving object, frequency of movements, the reaction time of choice, Romberg test, concentration and switching of attention according to the Bourdon test. For the analysis, 24 measurements of psycho-physiological indicators of the researched sportswoman were compared with corresponding indicators of highly skilled healthy karate girls, 29 people in total. The measurements of the studied athlete`s indicators were performed during the annual macrocycle at the beginning of a series of shock microcycles, which meant that she was in her optimal physical and psychological shape. It was found that the studied karate person has an invalid type of nervous system, which is not typical for this sport. Work efficiency, speed of work and mental stability also differ in favour of healthy karate women.